Is temporal summation of pain and spinal nociception altered during normal aging?. Issue 10 (October 2015) - Marouf, Rafik; Piché, Mathieu; Rainville, Pierre
Abstract : Abstract: This study examines the effect of normal aging on temporal summation (TS) of pain and the nociceptive flexion reflex (RIII). Two groups of healthy volunteers, young and elderly, received transcutaneous electrical stimulation applied to the right sural nerve to assess pain and the nociceptive flexion reflex (RIII-reflex). Stimulus intensity was adjusted individually to 120% of RIII-reflex threshold, and shocks were delivered as a single stimulus or as a series of 5 stimuli to assess TS at 5 different frequencies (0.17, 0.33, 0.66, 1, and 2 Hz). This study shows that robust TS of pain and RIII-reflex is observable in individuals aged between 18 and 75 years and indicates that these effects are comparable between young and older individuals. These results contrast with some previous findings and imply that at least some pain regulatory processes, including TS, may not be affected by normal aging, although this may vary depending on the method. Abstract : Aging is accompanied by reduced efficacy of inhibitory processes and preserved facilitation of pain and spinal nociceptive responses.